A Study on the Teaching and Instructional Design of Pattern Arrangement Principles in “Plane Composition” through Weaving Drafts - Li, Jhih-Jia; Wang, Lan-Ting; Chen, Wei-Han (Advances in Social Sciences Research Journal, 2026)
This study focuses on weaving drafts as the core research subject, exploring their application value in the pattern arrangement principles of plane composition and instructional design. The research samples were selected from the Tie-ups in Straight Twill, Crepe, and Dice Weaves in The Weaver’s Book of 8-Shaft Patterns. A total of 55 samples were collected and analyzed. Threading draft and Treadling were used as structural references to examine the correspondence between the visual composition of weaving drafts and the arrangement in graphic design. The research methodology consists of two aspects. From the perspective of plane composition, seventeen compositional principles were applied to analyze pattern characteristics, including symmetry, rotation, displacement, translation, and black–white inversion. From the perspective of instructional design, this study investigates how weaving drafts can be transformed into teaching content for plane composition, constructing a framework for pattern analysis and teaching that can be applied in basic design courses. The results indicate that weaving drafts not only possess clear structural logic in weaving construction but also exhibit a high degree of visual order and formal aesthetics. Among the compositional principles, black–white inversion, translation, reflection, and rotation are the most frequently observed, demonstrating regularity, symmetry, and variation in pattern generation. Furthermore, weaving drafts can serve as concrete and systematic visual teaching materials in plane composition. Through the correspondence among Tie-ups, Threadling draft, and Treadling, students are able to better understand the relationship between abstract compositional principles and actual patterns, thereby enhancing their compositional ability and formal interpretation in graphic design.